2012
DOI: 10.3109/10428194.2012.729056
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and distribution of lymphoma types in a tertiary care hospital in South India: analysis of 5115 cases using the World Health Organization 2008 classification and comparison with world literature

Abstract: This study aimed to analyze the distribution of lymphoid neoplasms in a single tertiary care center in India using the World Health Organization (WHO) 2008 classification. Histological material of 5115 patients with histopathological diagnosis of lymphoma, diagnosed over a period of 10 years (2001-2010), was analyzed retrospectively. Hodgkin lymphoma (HL) constituted 21.3% (n = 1089) and non-Hodgkin lymphomas (NHLs) constituted 78.7% (n = 4026). Of these, B-cell neoplasms accounted for 78.6% (n = 3166) and T-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
36
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 27 publications
11
36
2
Order By: Relevance
“…Other studies from the developing world have also reported lower median ages in B-NHL patients. 19,20,34,42 Our finding that B-NHL occurs at an earlier age seems to correlate with a lower gross domestic product in the developing world, 43 and suggests that socioeconomic factors may play a role in lymphomagenesis. The much lower median age of patients with HG B-NHL observed in SAF can be attributed to HIV infection, which predominantly affects young blacks.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Other studies from the developing world have also reported lower median ages in B-NHL patients. 19,20,34,42 Our finding that B-NHL occurs at an earlier age seems to correlate with a lower gross domestic product in the developing world, 43 and suggests that socioeconomic factors may play a role in lymphomagenesis. The much lower median age of patients with HG B-NHL observed in SAF can be attributed to HIV infection, which predominantly affects young blacks.…”
mentioning
confidence: 76%
“…16 Other studies from developing countries have reported a similar distribution pattern of Bcell lymphoma, with a high relative frequency of DLBCL and a low frequency of FL. [17][18][19][20] These differences are likely multifactorial in origin. In North America, whites have the highest incidence of FL of all races.…”
Section: B-cell Lymphomasmentioning
confidence: 99%
“…B-cell NHL make up 80-85% of all NHLs in India [10,13,14] . Diffuse large B-cell NHL is the most common subtype (60%) followed by indolent lymphoma (12-20%).…”
Section: Subtypes Of Nhlmentioning
confidence: 99%
“…The incidence and distribution of T-and NK-cell lymphomas in several Asian countries is summarized in Fig. 1 and Table 1 [ [4][5][6][7][8][9][10][11][12][13][14][15].The frequencies of T-and NK-cell lymphomas seem to increase from West to East Asia. The occurrence rate of Tand NK-cell lymphomas are relatively low (\20 % of NHL) mainly in West Asia (Turkey 16.2 %, Iraq 19 %, and Kuwait 18 %) and South Asia (Pakistan 11.3 %, and India 20.2 %), but relatively high mainly in East Asia (China 32.5 %, Korea 22 %, and Japan 24.9 %) and Southeast Asia (Thailand 25 %).…”
mentioning
confidence: 99%
“…The incidence and distribution of T-and NK-cell lymphomas in several Asian countries is summarized in Fig. 1 and Table 1 [ [4][5][6][7][8][9][10][11][12][13][14][15].…”
mentioning
confidence: 99%